2022
DOI: 10.3390/jmmp6050095
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Properties of AZ31B to AA6061 Dissimilar Joints Fabricated by Refill Friction Stir Spot Welding

Abstract: Dissimilar friction stir spot welds (FSSW) between the magnesium and aluminum alloys are joined, using a novel approach called refill friction stir spot welding. The present work aims to evaluate the macrostructural and mechanical properties of refill friction stir spot welded AZ31B and AA 6061-T6 alloys in two combinations, i.e., identical Mg-to-Mg and dissimilar Mg-to-Al joints, and the results are compared with the results obtained in conventional friction stir spot welding. The hardness profiles of the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…A significant increase in the hardness of the SZ A typical W-shape of Vickers hardness profiles was observed with a symmetrical profile to the center line of the keyhole for all the examined FSSW specimens. The same general shape has been observed in previous studies [26][27][28]. A gradual decrease in the Vickers hardness was observed in the HAZ due to the coarse grains caused by the frictional heat effect.…”
Section: Tensile-shear Strengthsupporting
confidence: 88%
“…A significant increase in the hardness of the SZ A typical W-shape of Vickers hardness profiles was observed with a symmetrical profile to the center line of the keyhole for all the examined FSSW specimens. The same general shape has been observed in previous studies [26][27][28]. A gradual decrease in the Vickers hardness was observed in the HAZ due to the coarse grains caused by the frictional heat effect.…”
Section: Tensile-shear Strengthsupporting
confidence: 88%
“…Despite the greater hardness, the reported weld strength values are lower than the AZ31B alloy's base mechanical characteristics. [39][40][41][42] This disparity may be due to texture deterioration caused by the welding process. Texture alterations can affect the anisotropic behaviour of the material, perhaps resulting in strength differences even when the hardness is quite high.…”
Section: Failure Mechanisms Of the Jointsmentioning
confidence: 99%
“…They suggested that the worn shoulder surface reduced the lap shear strength of the joints while all the tested welds surpassed the minimum standard lap shear strength requirements for aeronautical applications [80]. Numerous studies are available in the literature investigating the RF-SSW of various aluminum alloys such as AA7075 [95][96][97], AA7050 [98], AA2024 [99,100], AA2198 [80], AA2014 [101], AA6061 [102,103], AA2219 [93], dissimilar Al alloys [102,104], dissimilar Al/steel [105], Mg alloys [9,106,107], dissimilar Mg, and steel [7].…”
Section: Friction Stir Spot Weldingmentioning
confidence: 99%